THE EFFECT OF ADVERTISING AND SALES PROMOTION ON CONSUMER PURCHASE DECISIONS ON TIKTOK SHOP - Nurhayati Nurhayati (Universitas Dharmawangsa Medan, 2023)
ABSTRACTThis research aims to identify Sales promotions are a form of direct promotion that offers customers additional incentives or value for a product. Sales promotions encompass a wide range of tools, primarily those designed to encourage a faster or stronger market response. One of the best ways to communicate with customers is through promotions. And one of the ways most often used by marketing to introduce goods to customers is advertising. Researchers used Slovin's idea as a sampling technique. Current advertising is positive but not significant to purchasing decisions. This may be due to too much ineffective promotion or a lack of it. Interesting advertisement. Today, sales promotions through discounts and contests and events strongly influence purchasing decisions; this must be maintained and improved. Consumers today are more motivated to buy goods on Tiktok stores through discounts rather than contests or events held.Keywords: Advertising, Sales Promotion, Purchase Decisions